2020
DOI: 10.1177/0042098019894277
|View full text |Cite
|
Sign up to set email alerts
|

Contractual arrangements and entrepreneurial governance: Flexibility and leeway in urban regeneration projects

Abstract: Urban regeneration projects involve complex contractual deals between public- and private-sector actors. Critics contend that contracts hamper opportunities for flexibility and change in these projects due to strict provisions that are incorporated in legal agreements. This article offers contrary empirical insights based on a study of contractual arrangements for urban regeneration projects in the Netherlands, including an analysis of interviews and confidential documents. It zooms in on provisions on safegua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…However, thirdly, contrary to the research of van den Hurk and Tasan-Kok (2020) which focused on contracts between developers and municipalities, this research examined participatory processes. The flexibility of contracts provided opportunities for residents to adjust agreements, but also made the position of residents precarious.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, thirdly, contrary to the research of van den Hurk and Tasan-Kok (2020) which focused on contracts between developers and municipalities, this research examined participatory processes. The flexibility of contracts provided opportunities for residents to adjust agreements, but also made the position of residents precarious.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, secondly, this study has shown that agreements can be adjusted. As van den Hurk and Tasan-Kok (2020) showed in their research on contracts between municipalities and developers, contracts are flexible tools. Non-legal agreements in Oostenburg-Noord and Neue Mitte Altona helped to deliver outcomes of participatory processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the outcomes of neoliberal urban regeneration have taken centre stage, another strand of research has shed light on the changing relationship between the state and the market. In many places around the globe, urban regeneration projects rely heavily on public–private partnerships (Couch et al, 2011; Unsal, 2015; van Den Hurk and Tasan-Kok, 2020). Cities have adopted entrepreneurial mechanisms to ‘make costly redevelopment projects “pay for themselves”’ (Weber, 2002: 537).…”
Section: Conceptual Framework: Neoliberal Urban Regenerationmentioning
confidence: 99%
“…En un sentido más amplio, las razones que justifican el interés de la política urbana europea son varias. Primero, la novedad del tema, puesto que hasta hace poco la política urbana entendida como una política explícita de o para las ciudades estaba presente en la agenda política de pocos países (Van der Berg et al, 2018). Segundo, se trata de una política relevante por su potencial alcance, puesto que más del 70 % de los ciudadanos europeos vive en ciudades.…”
Section: Introductionunclassified